Automated evaluation of ANA under real-life conditions. Issue 1 (24th April 2017) - Loock, Clemens Dario; Egerer, Karl; Feist, Eugen; Burmester, Gerd-Rüdiger
Abstract : Introduction: Visual evaluation of indirect immunofluorescence (IIF) on human epithelial-2 cells is the routine method for screening for antinuclear antibodies (ANA) in connective tissue diseases. Since visual IIF is time-consuming and subjective, automated IIF processors have been developed to offer standardised, valid and cost-efficient IIF assays. Objective: The aim of this study was to determine the diagnostic reliability of 2 widely used IIF processors (Aklides, Medipan GmbH and Helios, Aesku Diagnostics) under real-life laboratory working conditions. Methods: ANA were determined in samples from patients with suspected autoimmune rheumatic disease (n=1008) using both automated IIF processors and compared with the results obtained by visual interpretation. The performance of IIF processors to discriminate positive from negative samples, pattern recognition and end point titre prediction were evaluated. Results: The IIF processors showed moderate agreement with visual interpretation in discriminating positive from negative ANA samples (κ values: Aklides 0.494; Helios 0.415). The sensitivity/specificity was 89%/59% for Aklides and 87%/54% for Helios. However, both processors correctly identified 99% of definitely positive samples (titre ≥1:320). Aklides correctly identified 43% of fluorescence patterns and its light intensity values showed good correlation (Spearman's ρ=0.680) with visually obtained titres. Conclusions: Automated IIF determination under real-life laboratory working conditions remains a challenge. Owing to their high sensitivity at clinically relevant ANA titres, automated IIF processors can already support but not totally replace visual IIF.